Comparison of AES and DES Algorithms Implemented on Virtex-6 FPGA and Microblaze Soft Core Processor - G. Renuka; V. Usha Shree; P. Chandra Sekhar Reddy (Institute of Advanced Engineering and Science, 2018)
Encryption algorithms play a dominant role in preventing unauthorized access to important data. This paper focus on the implementations of Data Encryption Standard (DES) and Advanced Encryption Standard (AES) algorithms on Microblaze soft core Processor and also their implementations on XC6VLX240t FPGA using Verilog Hardware Description language. This paper also gives a comparison of the issues related to the hardware and software implementations of the two cryptographic algorithms.